Nursing Care in the Case of Infants with Acute Respiratory Infections with Ineffective Airway Nursing Problems: A Case Study - Leni Agustin; Hamidah Retno Wardani; Dinda Oktaviani; Siti Riskika (Health and Technology Journal (HTechJ), 2024)
Acute respiratory infections that attack the upper and lower tract in a stimulant or sequential manner that lasts up to 14 days This can certainly result in the risk of inability to clear secretions or even obstruction of the airway. The purpose of the study was to provide nursing care to overcome patient problems. This research is a case study of 1 infant who experienced acute respiratory infection with the nursing problem of ineffective airway clearance for 3 days on May 15-18, 2023. The subject in this study was Baby. A who was male and 35 days old who was admitted to the pediatric ward (Melati) of Dr. H. Koesnadi Bondowoso Hospital with the main complaint of shortness of breath who met the inclusion criteria with data collection techniques of interviews, observation, physical examination and documentation studies. The instrument used is the pediatric nursing assessment form and the SOP for action according to applicable regulations. The results of this study were obtained from the assessment, namely ineffective airway clearance in accordance with the theory, and diagnoses in accordance with the client's condition. In implementation refers to nursing interventions using SIKI which are tailored to the client's condition as well as evaluation refers to the overview, goals and specific objectives that have been set. The evaluation results obtained complaints of tightness and reduced secretion production, RR: 46 x/min, SpO2: 98%.